2012
DOI: 10.1097/pec.0b013e318267a73d
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Diagnosis of Metaphyseal Forearm Fractures in Children

Abstract: We confirm that ultrasound is an applicable and safe alternative tool to x-rays in nondisplaced or excluded metaphyseal forearm fractures in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
17

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 12 publications
2
27
0
17
Order By: Relevance
“…48 In addition to eight articles that had not been published at that time, 20,[26][27][28]32,33,41,46 our study includes thirteen other articles not included in that review. 21,22,24,25,29,30,[34][35][36]38,41,43,44 Additional studies were possibly found as a result of a more comprehensive search strategy. Our review reaches similar conclusions, that PoCUS is a useful tool to supplement radiographs for the detection of fractures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…48 In addition to eight articles that had not been published at that time, 20,[26][27][28]32,33,41,46 our study includes thirteen other articles not included in that review. 21,22,24,25,29,30,[34][35][36]38,41,43,44 Additional studies were possibly found as a result of a more comprehensive search strategy. Our review reaches similar conclusions, that PoCUS is a useful tool to supplement radiographs for the detection of fractures.…”
Section: Discussionmentioning
confidence: 99%
“…All studies reported both the sensitivity and specificity of PoCUS, and LRs were calculated from these values when the authors did not include them in their manuscripts. Twenty-five studies 7,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][41][42][43][44] were included, ranging from 26 to 653 patients. Collectively, these studies included 2,982 patients and identified 1,200 fractures, with fracture prevalence ranging from 7% to 71% (aggregate prevalence of 40.2%).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Da kindliches Knochengewebe jedoch deutlich strahlensensibler als das des Erwachsenenalters ist, sollte jede unnötige ionisierende Strahlung vermieden werden. Zahlreiche Publikationen belegen mittlerweile den sinnvollen Einsatz der Sonographie im Rahmen der primären Frakturdiagnostik, und systematische Untersuchungen mit direktem Vergleich zur Röntgendiagnostik zeigen, dass die Sonographie bei bestimmten Frakturentitäten das Röntgen ergänzen oder sogar ersetzen kann [1][2][3][4][5][6]. Bei gleicher diagnostischer Qualität kann so die Zahl unnötiger Röntgenuntersuchungen reduziert werden.…”
Section: Sonographische Frakturdiagnostikunclassified